The Aesthetics of Decoloniality in Psychotherapy: Institutional Psychotherapy and Fanon’s Ethico-Aesthetic Paradigm - Faramelli, Anthony John (PORTO ARTE: Revista de Artes Visuais, 2020)
This article will examine how colonialism and racism stratifies space, with particular focus on aesthetic production and the way in which an individual’s freedom is dependent on the “ambience” of the space they occupy. The analysis will be grounded in Algerian colonial psychiatry and anti/de-colonial psychotherapy. Through an examination of Frantz Fanon’s application of Institutional Psychotherapy in Blida-Joinville Hospital, this article will argue that Fanon’s decolonial politics and his commitment to dis-alienation were reliant on the (re)construction of space within the hospital so as to increase what Félix Guattari would later refer to as the “coefficient of transversally”. By implication, this article’s argument intends to use Fanon’s spatial approach to psychotherapy in order to elicit a reading of Institutional Psychotherapy en masse as having, at its heart, a focus on spatial and aesthetic production. Resumo Este artigo examinará como o colonialismo e o racismo estratificam o espaço, com foco especial na produção estética e na forma como a liberdade de um indivíduo depende do "ambiente" do espaço que ele ocupa. A análise será fundamentada na psiquiatria colonial argelina e na psicoterapia anti/de-colonial. Através de uma análise do trabalho de Frantz Fanon da Psicoterapia Institucional no Hospital Blida-Joinville, este artigo argumentará que a política decolonial de Fanon e seu compromisso com a desalienação dependeram da (re)construção do espaço dentro do hospital. Isso também se soma ao que mais tarde Félix Guattari chamaria de "coeficiente de transversalidade". Por implicação, o argumento deste artigo pretende utilizar a abordagem espacial de Fanon para psicoterapia, a fim de obter uma leitura da Psicoterapia Institucional em massa como tendo, em seu cerne, um foco na produção espacial e estética.